Current Tendencies in ESP Didactics - Insights of an ESP Journal Editor - Stojković, Nadežda M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
English for Specific Purposes (ESP) is a demanding field for its practitioners regarding its methodology, pedagogy, didactics, for numerous factors, primarily, it having a paradoxical position within the field of English language teaching due to at once its undeniable presence and relevance but rare academia institutional establishment, and still not having a consolidated relevant theoretical basis. Practice of teaching ESP involves dealing with real life issues of how to teach a group of students who need this instruction for clearly pre-determined reasons, and therefore, what approach to use, which material, grammatical units, and alike. Stemming from actual teaching experiences, there appear valuable insights, opinions, research results of ESP practitioners as formulated and presented in the form of journal articles, which even more than in other fields become primary sources of familiarizing with current and emergent approaches in ESP didactics. As an Editor-in-Chief of an ESP scientific journal, the author presents discernible, most prominent tendencies in ESP methodology, pedagogy, didactics worldwide over, which summarize current theoretical and practical basis of this form of language teaching and intercultural communication.